The Probiotic Attributes and Anti-pseudorabies Virus Evaluation of Lactobacillus Isolates - Yang, Ming-Fan; Yan, Wei; Li, Yan; Li, Shuai-Qi; Chen, Hong-Ying; Yin, Qing-Qiang; Dang, Xiao-Wei; Zhang, Hong-Ying (Frontiers in Veterinary Science, 2022)
The emergence of pseudorabies virus (PRV) variants brings serious harm to the swine industry, and its effective treatments are limited at present. As one of the probiotics, the Lactobacillus species have beneficial characteristics of regulating the balance of intestinal flora, inhibiting the growth of pathogenic bacteria and viruses' proliferation, and improving self-immunity. In this study, Lactobacillus plantarum HN-11 and Lactobacillus casei HN-12 were selected and identified through morphology observation, Gram stain microscopy, 16S rRNA sequencing analysis, and specific amplification of the recA gene and pheS gene. All tested isolates exhibited rapid adaptation to the different conditions, excellent acid, and bile tolerance, and sensitivity to Salmonella, Staphylococcus aureus, and Escherichia coli. The antibiotic susceptibility assay displayed the isolates sensitive to most antibiotics and resistant to Lincomycin and Norfloxacin. Moreover, the supernatants of HN-11 and HN-12 inhibited PRV proliferation in ST cells. The results of animal experiments showed that supplementing the challenged mice with the supernatants of Lactobacillus isolates in advance delayed the course of the disease. PRV was detected in the heart, liver, spleen, lung, kidney, and brain tissues of dead mice in the test groups, and its copies in the lungs were significantly decreased compared with the control mice (P < 0.05). These findings proved the advantages of L. plantarum and L. casei as potential probiotic cultures, which could provide a basis for its application in microecological preparations and functional formulations.